Diagnostic Patterns of Suspected Covid-19 Patients Using Scor Covid-19, PCR Test and Serological Test in Dr. Soetomo Hospital Surabaya, Indonesia - Usman Hadi; Bramantono Bramantono; M Vitanata; Musofa Rusli; Brian Eka Rahman; Tripudi Asmarawati; Erika Marfiani; Erwin Astha Triyono (Universitas Airlangga, 2021)
Objective: To find out the diagnostic pattern of COVID-19 using RT-PCR or a rapid antibody test in the suspected group of patients.Method: The study was conducted in Dr. Soetomo General Hospital (referral hospital for covid-19, 1500 beds). The study used data on patients with suspected covid-19 who were hospitalized at the Dr. Soetomo General Hospital in Surabaya.Result: There were 200 suspected COVID-19 patients enrolled in this study, the main complaints of cough, fever, dyspnoea, around 69.5%, 75%, and 76.5%, respectively. Although not a common symptom, it seems that anosmia (14%) is typical for COVID-19. Based on this scoring system, a total of 196 patients had a high risk of being infected with COVID-19, and 125 (64%) of them finally showed a positive PCR test. PCR test mostly positive (62.5%), while serological test (rapid immunoglobulin test) mostly nonreactive, but there were no significant differences between PCR and Serological test (p=0.16 OR: 1.5(0.84-71). Furthermore, if we compare the various existing variables, namely the covid-19 score, immunoglobulin rapid test, and radiological examination, only the radiological examination results can be used as a strong predictor of positive PCR results (p=0.005, OR: 1.68 (0.17-16.43).In this study, we found that abnormal chest radiographs are a good parameter for diagnosing COVID-19, (OR: 2.92; 95% CI, 1.34 -6.34).Conclusion: The initial radiological examination combined with the clinical symptoms of Covid-19 is the most important thing to predict the presence of this disease.